ASPEK NILAI MORAL DALAM AKUN FACEBOOK JOKOWI - Santoso, Joko; Sabardila, Atiqa; Wahyudi, Agus Budi; Haryanti, Dwi; Faizah, Naimul; Riyanto, Sugeng (Jurnal Penelitian Humaniora, 2017)
This study aims at (1) identifying the lingual form of disfemism in Joko Widodos Facebook account; (2) describing the addressing form containing sarcasm in Joko Widodos official Facebook account; and (3) identifying the sarcasm expression used by the operator and the uploader of the account. The object of this study is polite expressions. Linguistic unit of the expressions can be in the form of word, phrase, clause, and sentence. The data of this present study are sentence or sentences in Jokowis official Facebook account that contains positive connotation words. The data contexts of this research are discourse containing positive connotation sentences, the topic of discourse written by people in Jokowis account, the identity of the participant, and the context of extra-lingual that is based on the importance of the operator of the presidents social media account. The data collection was conducted through documentation technique. The data in Jokowis official account were copy-pasted. Then, the data were being read intensively to note the positive connotation utterance. The data analysis was conducted through referential (identity) method, pragmatic (identity) method, translational (identity) method, and articulatory phonetic (identity) method. The referential (identity) method was used to identify the topics that were stated by the uploader of the account. The pragmatic (identity) method was used to identify the background of (profession, organization etc) that appeared in their writings. The translational (identity) method was used in describing the origination of the language they use. It is possible that through the use of this method, this study finds the register on that account. Finally, the phonetic (identity) method was used to identify the utterance characteristic they stated. The positive or negative emotion of the speaker, usually, marked by the special pronunciation. To establish the data analysis, this study uses distributional method: substitution technique and paraphrase technique. Based on the data analysis, this study shows several results. First, the euphemism utterance in Jokowis official Facebook account using any levels, i.e. word, phrase, clause, and sentence. Through those levels, the writer presents suggestions and critics to the owner of the account Joko Widodo. Second, the functions that are stated through that account are expression device, communication relationship to the leader, integration device, and self-control device. Third, the topics stated by the people in that account are about the depiction of Joko Widodo that in their opinion, Joko Widodo shows pretending, the existence of Megawati in the election of Joko Widodo as a president, the increasing of IDR currency and other things at the beginning of his leadership. The expression shows hatred towards the elected president. Furthermore, they also express about Jokowis unability to establish the IDR currency and his leadership is judged as not good. In addition, to the people, especially netizen are invited to disbelieve to his leadership.